Two new Prenolepis species (Hymenoptera: Formicidae) from Indomalaya and Australasia, with a redescription of P. dugasi from Vietnam - Williams, Jason L.; Lapolla, John S. (Zootaxa, 2018)
Prenolepis is a lineage of formicine ants with its center of diversity in the Old World tropics. Three more Prenolepis species are added to the Indomalayan and Australasian fauna and another is synonymized, bringing the total number of Prenolepis species worldwide to 19. Two new species are described: P. nepalensis from Nepal and P. lakekamu from Papua New Guinea, the latter being the first in the genus east of Wallace’s Line. Additionally, P. dugasi Forel (comb. rev.) from Vietnam is transferred from Nylanderia and redescribed. Based on morphology, each of the three species appears to be most closely-related to other species found predominantly in or nearest to their respective bioregions: P. nepalensis most resembles P. darlena, P. fisheri, and P. fustinoda; P. lakekamu bears strongest resemblance to P. jacobsoni, P. jerdoni, and P. subopaca; and P. dugasi most resembles P. melanogaster. Descriptions, illustrations and images are provided for all three species. One new synonymy is proposed: P. angulinoda Chen & Zhou 2018 = P. fustinoda Williams & LaPolla 2016. An updated key for workers of all extant Prenolepis species is also included.